Reasons for Webcam Usage Preferences of Grade 12 Students during Synchronous Meetings - Martin, Ciro Luis T. (Animo Repository, 2022)
The COVID-19 pandemic has caused several issues in different sectors of the world, and education is one of the most affected areas, with students and teachers being obliged to continue their schooling through online education. It raised an issue about students’ virtual presence, specifically their webcam usage. The majority of related studies focused on the perceptions of teachers and university students of the impacts, benefits, and drawbacks of webcam use during synchronous classes. However, there are insufficient studies that examined the high school students’ reasons for turning their webcams on or off during synchronous meetings. This prompted the researchers to conduct a descriptive quantitative study to determine the reasons for webcam usage preferences of Grade 12 online-based learning (OBL) students enrolled in Saint Louis University Laboratory High School – Senior High for the first semester of 2021-2022. 262 Grade 12 OBL students participated in the survey administered through Google Forms. Frequency counting, percentage, and weighted mean were used to analyze the data. Findings show that 88.93% of the students prefer to turn off their cameras due to privacy concerns, appearance, background, household chores, technical problems, and anxiety-related matters. Meanwhile, 11. 07% of the students prefer to turn their cameras on to show respect and participation. Other reasons include being confident not to cause distraction, being comfortable with their study space, trusting the school’s data privacy, and having a stable internet connection. These findings could help the teachers figure out how to encourage virtual presence in synchronous class sessions while considering inclusivity.